L'incoronazione celeste nel mondo Bizantinon : politica, cerimoniale, numismatica e arti figurative - Torno Ginnasi, Andrea (Archaeopress archaeology, 2014)
This study deals with the iconographic theme of imperial Byzantine 'heavenly coronation', or André Grabar's couronnement symbolique, with particular attention to fine arts and numismatics. This theme, along with the rituals of imperial investiture, represents the concept of divine kingship in figurative terms, a significant ideological premise for Byzantine theocracy